Design and optimization of a butterfly-shaped grafting clip and cutting mechanism based on finite element simulation - Qiangwen Su; Letian Wu; Qiuxing Yue; Xingdong Gao; Xinwei Cao; Huifeng Shi (PLoS ONE, 2026)
To improve the reliability and cost-efficiency of the grafting mechanism, this study proposes a novel butterfly-shaped polyethylene (PE) grafting clip and integrated cutting-type clip-feeding mechanism. The proposed system replaces traditional steel coil clips and vibration screen feeders with a lightweight, low-damage, and low-cost design capable of continuous clip feeding. The mechanical behavior of the PE clip material was characterized through tensile testing and modeled using the Johnson-Cook constitutive equation. A finite element model of the cutting process was established in Abaqus to investigate the effects of cutting force, speed, and angle on blade stress and clip deformation. Using the Box-Behnken response surface methodology, the cutting parameters were optimized to minimize stress concentration and material distortion. Simulation results showed that optimal performance was achieved at a cutting force of 110 N, a speed of 25.618 cm/s, and a cutting angle of 32.414 ° , yielding a maximum blade stress of 1.31 MPa and clip strain of 5.304%. Validation tests demonstrated that a 30 ° cutting angle produced the highest cutting quality, consistent with simulation predictions. Comparative performance evaluations with a commercial vibrating screen clip feeder confirmed the superiority of the proposed system in terms of reliability, energy efficiency, operational noise, and cost. The developed mechanism offers a compact and practical solution for automated grafting, particularly suitable for small and medium-sized seedling nurseries seeking affordable mechanization technologies.